An interesting case of Contarini’s syndrome in a young patient - Abhishek Agarwal; Armaan Singh; Ambikesh Gupta; Anish Goyal (International Journal of Research in Medical Sciences, 2026)
Pleural effusion is a common disease of the pleura. The pleural effusion is usually unilateral and bilateral pleural effusion is less commonly seen. In bilateral pleural effusions usually the same etiology is present on both the sides but bilateral pleural effusions due to the two different etiologies on the two sides is rare. Here we are describing an interesting case of Contarini’s syndrome where exudative pleural effusion was present on each side but due to the two different etiologies on the two sides.